Developing an Interactive Multimedia of Emergency Stretcher Subject in Extracurricular Activities of Scouting for Students with Hearing Impairment on Special Education Senior High School - Muhamad Izhar Safawi; Sihkabuden Sihkabuden (Department of Special Education, 2017)
Students with hearing impairment have hearing obstacle bringing complex impact, especially for the intellectual nuisance and communication obstacle that related to language and vocabulary. The purposes of this development was producing an interesting of multimedia interactive materials of emergency stretcher for students with hearing impairment. Method that use on this research and development was adapted from Borg and Gall (1989) models. The results showed that product was valid. The research results from material expert was obtained score 91% (very feasible), media expert 98% (very feasible), practitioner 84.5%, the results of small group test was divided into two phases. They were phase I, learning with the help and guidance of teachers or coaches was obtained score 89.9% with the criteria of highly effective. Phase II, learning without the help and guidance of teachers or coaches was obtained score 75.8% with the criteria of effective and could be used according to a small group test. The results showed that product was valid, very decent and very effectively used with help and guidance teachers or coaches. The conclusion of this research was resulting a product including with criteria of being good and could improve cognitive abilities students with hearing impairment.